The outbreak of SARS-CoV-2 pneumonia calls for viral vaccines - Shang, Weilong (NPJ Vaccines, 2020)
The outbreak of 2019-novel coronavirus disease (COVID-19) that is caused by SARS-CoV-2 has spread rapidly in China, and has developed to be a Public Health Emergency of International Concern. However, no specific antiviral treatments or vaccines are available yet. This work aims to share strategies and candidate antigens to develop safe and effective vaccines against SARS-CoV-2.